Antropolinguistic Study In Cultural Terms Of Java Traditional Bride Meeting Processes - Feri Indra Setiawan (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2022)
This study aims to describe language terms about culture or other expressions, describe the naming process in language, describe politeness in language; and describe ethnicity from the point of view of language. The approach used in this research is a theoretical and methodological approach with descriptive qualitative research. The analysis technique uses descriptive qualitative analysis. The results of this study obtained data on language terms about culture or other expressions found in the Javanese traditional wedding procession which has a strong influence on Java because it uses the Kawi language. Meanwhile, in the modern wedding procession, Javanese and foreign terms are found. Furthermore, the term naming process in language at the bridal gathering procession was found to be in the form of using words that are considered more contemporary than using standard Indonesian words, this is due to cultural shifts and lifestyles that occur in society. In addition, the use of language that is in accordance with the elements of politeness is in the form of Saman, Panjenengan, Priyai, Pini Elder, Hadi Elder and Pepunden. The conclusion obtained in this study is that the Javanese traditional wedding meeting has more cultural terms, naming, politeness and cultural entities in terms of Kawi language which is used to preserve ancient Javanese culture which is not widely practiced. Meanwhile, in modern traditional weddings, they rarely use standard Indonesian or often use foreign languages ​​to make them seem more contemporary and also use Javanese language with the intention of adding to the polite impression of the procession.